2021
DOI: 10.1101/2021.06.05.21258365
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early epidemiological signatures of novel SARS-CoV-2 variants: establishment of B.1.617.2 in England

Abstract: The rapid emergence of SARS-CoV-2 mutants with new phenotypic properties is a critical challenge to the control of the ongoing pandemic. B.1.1.7 was monitored in the UK through routine testing and S-gene target failures (SGTF), comprising over 90% of cases by March 2021. Now, the reverse is occurring: SGTF cases are being replaced by an S-gene positive variant, which we associate with B.1.617.2. Evidence from the characteristics of S-gene positive cases demonstrates that, following importation, B.1.617.2 is tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 29 publications
2
84
0
Order By: Relevance
“…Efforts to increase population's confidence and willingness to be vaccinated will thus be of paramount importance to allow a return to a pre-COVID-19 lifestyle. Our study shows that the spread of new more transmissible (and possibly also more lethal [35][36][37][38][39][40][41][42] ) variants substantially increases herd immunity thresholds to level that may not be feasible in any population, so that mitigation strategies become much more relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to increase population's confidence and willingness to be vaccinated will thus be of paramount importance to allow a return to a pre-COVID-19 lifestyle. Our study shows that the spread of new more transmissible (and possibly also more lethal [35][36][37][38][39][40][41][42] ) variants substantially increases herd immunity thresholds to level that may not be feasible in any population, so that mitigation strategies become much more relevant.…”
Section: Discussionmentioning
confidence: 99%
“…We consider a basic reproductive number (R0) of 2.5 according to estimates for the historical SARS-CoV-2 lineages in China [19][20][21]62 . Higher values (in the range 3.8-6) are used when other variants of concern are modeled [35][36][37][38][39][40][41][42] .…”
Section: Sars-cov-2 Transmission and Vaccination Modelmentioning
confidence: 99%
“…We also identified 22 patients with COVID-19 caused by B.1.617.1 (Kappa) or B.1.617.2 (Delta) variants reported to be causing widespread disease and extensive public health problems in India, other Southeast Asian countries, and many regions of the UK (https://www.who.int/publications/m/item/weekly-epidemiological-update-on-covid-19---8-june-2021, last accessed June 9, 2021). [43][44][45][46][47][48][49][50] These patients also had a high rate of hospitalization.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In the last half of May, depending on the specific day, the B.1.1.7 variant caused 63%-90% of J o u r n a l P r e -p r o o f new COVID-19 cases. In addition, we found that cases caused by variants P. [43][44][45][46][47][48][49][50] Variant B.1.617 is resistant to the monoclonal antibody Bamlanivimab (LY-Cov555), as assessed by an in vitro host-cell entry assay, 46 and B.1.617.1 has been reported to be highly virulent in hamsters following intranasal inoculation. 45 These two variants are characterized by a core group of amino acid replacements in spike protein: L452R, T478K or E484Q, D614G, and P681R (Figure 6).…”
Section: Epidemiologic Trajectory and Patient Overviewmentioning
confidence: 99%
See 1 more Smart Citation